The abandoned empress. 2 - 인아 (Yen Press, 2022)
In an attempt to cut ties with the Imperial family, Aristia la Monique decides to strengthen her bonds to her own. But being named the official heir of family Monique means first becoming a knight worthy of leading the Second Order -- no easy feat for someone born with such a delicate constitution. And when unrest in the borderlands takes her father and mentors away, she's left without a teacher to oversee her training. With time quickly running out and all the cards stacked against her, will Aristia succeed in this desperate scramble to escape her fate?